2021
DOI: 10.1007/s00330-021-07826-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative CT radiomics-based models for prediction of haematoma expansion and poor functional outcome in primary intracerebral haemorrhage

Abstract: Objectives To test radiomics-based features extracted from noncontrast CT of patients with spontaneous intracerebral haemorrhage for prediction of haematoma expansion and poor functional outcome and compare them with radiological signs and clinical factors. Materials and methods Seven hundred fifty-four radiomics-based features were extracted from 1732 scans derived from the TICH-2 multicentre clinical trial. Features were harmonised and a correlation-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 48 publications
3
22
1
Order By: Relevance
“…On the other hand, the location-specific Rad-score that took into account the potential interaction between Rad-score and haematoma location can help predict poor outcomes at 6 months. Most recently, several studies suggested that NCCT radiomics features of haematomas could improve the predictive performance of prognostic models ( Pszczolkowski et al, 2021 ; Song et al, 2021b ). Nevertheless, the differences in radiomics features by haematoma location were not considered in these models, which may be valuable for proof-of-concept studies ( Anderson et al, 2010 ; Fu et al, 2014 ; Qureshi and Qureshi, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the location-specific Rad-score that took into account the potential interaction between Rad-score and haematoma location can help predict poor outcomes at 6 months. Most recently, several studies suggested that NCCT radiomics features of haematomas could improve the predictive performance of prognostic models ( Pszczolkowski et al, 2021 ; Song et al, 2021b ). Nevertheless, the differences in radiomics features by haematoma location were not considered in these models, which may be valuable for proof-of-concept studies ( Anderson et al, 2010 ; Fu et al, 2014 ; Qureshi and Qureshi, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed classification of hypodensity signs may improve accuracy; however, this had limited clinical applicability among doctors with insufficient clinical experience. Several recent studies ( Nawabi et al, 2021 ; Pszczolkowski et al, 2021 ; Song et al, 2021 ) have shown that radiomics, which applies machine learning (ML) algorithm, may be a more efficient and objective method for evaluating outcomes in patients with ICH. The ML method for evaluating the prognosis of patients with ICH remains in its infancy and has unstable models.…”
Section: Discussionmentioning
confidence: 99%
“…A review ( Morotti et al, 2019 ) was conducted regarding the detection, interpretation, reporting, and status of these markers, which may extensively improve their clinical application. With the advent of artificial intelligence (AI), radiomic methods have been extensively applied to predict the prognosis and HE of patients with ICH ( Shen et al, 2018 ; Xie et al, 2020 ; Xu et al, 2020 ; Pszczolkowski et al, 2021 ; Song et al, 2021 ). However, this method remains in the research phase; moreover, its predictive performance should be further verified.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the application of radiomics can extract more objective features that are not retrievable based on vision and manual measurements. It has consistently been shown to be effective for the prediction of hematoma expansion and poor neurologic outcome in spontaneous IPH patients [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. As for traumatic IPH, we herein demonstrated its usefulness to further expand the limited evidence currently available [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning models generated from selected radiomics features have been shown to correlate well with clinically important diagnostic or prognostic outcomes [ 20 ]. Focusing on spontaneous intracerebral hemorrhages, extensive studies have been performed, which demonstrated the good predictive capability of models derived from radiomics features for hematoma expansion [ 21 , 22 , 23 , 24 , 25 ] and poor neurological outcome [ 24 , 26 , 27 , 28 , 29 , 30 ]. Furthermore, increased c-statistics were observed after the radiomics features were combined with clinical and radiological parameters constantly.…”
Section: Introductionmentioning
confidence: 99%